2013
DOI: 10.1111/1365-2656.12129
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of biotic resistance across complex life cycles

Abstract: Summary1. Biotic resistance is the ability of communities to inhibit the establishment, spread or impact of novel species. However, the interactions that underlie biotic resistance depend heavily on the contexts in which species interact. Consequently, studies of biotic resistance that consider single processes, patches, species or life-history stages may provide an incomplete picture of the capacity for communities to resist invasion. 2. Many organisms have multiphasic life cycles, where individuals can occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Predation studies have demonstrated that generalist native predators play an important role in biotic resistance to non-native species in marine communities (de Rivera et al, 2005;Dumont et al, 2011a;Freestone et al, 2013;Rius et al, 2014). Predators can limit the abundance and distribution of non-native marine species that may lack effective defenses (de Rivera et al, 2005;Dumont et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Predation studies have demonstrated that generalist native predators play an important role in biotic resistance to non-native species in marine communities (de Rivera et al, 2005;Dumont et al, 2011a;Freestone et al, 2013;Rius et al, 2014). Predators can limit the abundance and distribution of non-native marine species that may lack effective defenses (de Rivera et al, 2005;Dumont et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, more than 15 NIS have successfully established, ten of which arrived within the last two decades Bullard et al 2007a). In less explored areas such as South Africa, nine introduced and nine cryptogenic ascidian species have been recorded (Rius et al 2014b).…”
Section: Invasive Ascidians and Their Invasion Historymentioning
confidence: 99%
“…Aside from salinity, ascidians can also tolerate and survive a wide range of temperatures (Lambert 2005;Rius et al 2014b). For example, laboratory experiments showed that B. schlosseri and B. violaceus could survive water temperature at 10-25 and 5-25 °C, respectively (Epelbaum et al 2009).…”
Section: Broad Tolerance Of Environmental Conditionsmentioning
confidence: 99%
See 2 more Smart Citations